2005
DOI: 10.1139/x05-168
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal precipitation in the south-central Helan Mountain region, China, reconstructed from tree-ring width for the past 224 years

Abstract: Chinese pine (Pinus tabulaeformis Carr.) trees from the Helan Mountain range in central China have been used to reconstruct total January–July precipitation from AD 1775 to 1998. For the calibration period R2adj = 0.52. Narrow rings are associated with below-average precipitation from March through August. Wide rings are produced in years when the East Asian summer monsoon front arrives early. We use local historical writings over the last 300 years about extreme climatic conditions between spring and early su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 12 publications
10
47
0
1
Order By: Relevance
“…Inversely, increased temperature before and during the growth season inevitably strengthen the water stress by accelerating water consumption in the soil and trees through evaporation and transpiration, resulting in the formation of narrow rings, and vice versa. Reasonably, positive correlation of tree rings with monthly precipitation and negative correlations with monthly mean temperature in current growth year was identified in this study, and this climate-growth pattern was generally reported in the arid to semi-arid CLP (Gao et al, 2005;Liu et al, 2005; and other areas of northern China (Liang et al, 2007).…”
Section: Climate-growth Relationshipsupporting
confidence: 71%
See 2 more Smart Citations
“…Inversely, increased temperature before and during the growth season inevitably strengthen the water stress by accelerating water consumption in the soil and trees through evaporation and transpiration, resulting in the formation of narrow rings, and vice versa. Reasonably, positive correlation of tree rings with monthly precipitation and negative correlations with monthly mean temperature in current growth year was identified in this study, and this climate-growth pattern was generally reported in the arid to semi-arid CLP (Gao et al, 2005;Liu et al, 2005; and other areas of northern China (Liang et al, 2007).…”
Section: Climate-growth Relationshipsupporting
confidence: 71%
“…Among them, the 1876-1878 and 1927-1930 drought events ranked as two of the most severe natural disasters in Chinese history and have drawn significant attention from scientists due to their devastating consequences on society (Hao et al, 2010;Zhou et al, 2010). These two recent extremely dry events, the 1920s drought in particular, have been captured by many other tree-ring reconstructions in the CLP and other regions of China (Liu et al, 2003a(Liu et al, , b, 2005Liang et al, 2007;Chen et al, 2011aChen et al, , 2012Deng et al, 2013;Kang et al, 2013) as well as Mongolia (Pederson et al, 2001). The 1920s drought was also revealed by a weakened signal of the EASM indicated by a dry-wet mode index (Qian et al, 2012).…”
Section: Annual Inter-annual and Centennial Variation Of The Pdsimentioning
confidence: 84%
See 1 more Smart Citation
“…During the last 181 years, there were 33 extreme high-temperature years in the Hulunbuir Area, accounting for 18.3% of the study period. 1926-1928 and 1935-1937 were characterized by severe drought that led to tremendous loss of life in northern China, recognized by other studies (Liu et al 2005, Liang et al 2006, Cai et al 2008. The June-July mean maximum temperature reached the highest value in 1853, while the year with lowest mean maximum temperature in the past 181 years was 1868.…”
Section: Mean Maximum Temperature Reconstructionmentioning
confidence: 90%
“…These achievements helped researchers to understand the past climatic variations in China in the context of global climate change. For the north margin of the East Asian summer monsoon [16], high-resolution tree-ring records were used to reconstruct temperature [17] and precipitation [18][19][20][21][22] variations over the past few hundred years. The first tree-ring based precipitation prediction was also carried out [23], which has been proved to be largely consistent with real precipitation records until now.…”
mentioning
confidence: 99%